Ahlus Sunnah Views of COVID-19 in Social Media: The Islamic Preaching by Gus Baha and Abdus Somad - Saifuddin Zuhri Qudsy; Achmad Fawaid; Althaf Husein Muzakky (Al-Albab, 2021)
The Covid-19 pandemic, which occurred in line with the massive transformation of digital media, was a significant moment that enabled diverse Islamic preachers to use media to advance their own interests. However, little has been discussed regarding the religious responses to the COVID-19 performed by Ahlus Sunnah community members or those who are not inclined to participate in radical activities. By analyzing two important Ahlus Sunnah figures, Gus Baha and Abdus Somad, this article focuses on the group’s COVID-19 views on social media, which represents their motives, perspectives, strategies, and theological views to encourage Muslims to have certain mindsets on the virus. Given that Abdul Somad Official account around $1400- 21,700 per month with 950 thousand subscribers and Gus Baha Official account around $5-75 with 500 thousand subscribers, this article investigates their religious/ theological perspectives on COVID-19 and the extent to which they represent religious moderate viewpoints as the solution of the COVID-19. It argues that their YouTube or Facebook channels have enabled the birth of religious moderate arguments on COVID-19 rooted in the Ahlus Sunnah movement. Unlike well-established scientific perspectives on Covid-19 that spread out through official government channels or television, Gus Baha and Abdus Somad’s viewpoints have been relatively independent from medical networks, but highly dependent on Ahlus Sunnah movements. With a high number of offline and online followers, it demonstrates the potential of their status as religious influencers on COVID-19 based on Ahlus Sunnah viewpoints in Indonesia.